Terminology for Children in Sumerian Administrative Records - Bartash, Vitali (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Region: Southern Mesopotamia = Sumer. Period: Ca. 3200-2000 BC, i.e. Early Bronze Age. Sources: Administrative cuneiform texts from temple and palace archives. Subject: Children of low-rank social status in temple and palace households. Aims: 1) Systematize the terminology for children and offer an overview of its development. 2) Identify what biological social characteristics of children are hiding behind these terms. 3) Recognize the characteristic features in the terminology for children. Methods: Philological, historical, sociological (sex-age groups/classes). Key facts: 1) Children as dependents in central households appear in cuneiform records as early as the Uruk IV Period (ca. 3350-3250 BC). 2) The documents enable to reconstruct several sets of terms to describe human resources in temple and palace households. A substantial part of these terms describe two main biological characteristics of children: their sex and age group. 3) Originally, during the earliest periods, the terminology for humans and children in particular bore a strong resemblance with the terms for animals, which implies that the former is an offshoot of the latter. Main point: Other age groups, adults and elderly, received specific terms that were reserved exclusively to designate these age groups. The striking fact conclusion about the child terminology is that it obstinately remained dependent on the terminology for animal youth. The comparison of the bureaucratic terms for children with the lexical evidence (“ancient dictionaries”) demonstrates that the rich selection of terms within the field “children/childhood” that existed in the Sumerian society did not find reception in the administrative practice.